2015
DOI: 10.1016/j.exger.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The adipokine leptin mediates muscle- and liver-derived IGF-1 in aged mice

Abstract: Muscle- and liver-derived IGF-1 play important roles in muscle anabolism throughout growth and aging. Yet, prolonged food restriction is thought to increase longevity in part by lowering levels of IGF-1, which in turn reduces the risk for developing various cancers. The dietary factors that modulate IGF-1 levels are, however, poorly understood. We tested the hypothesis that the adipokine leptin, which is elevated with food intake and suppressed during fasting, is a key mediator of IGF-1 levels with aging and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Similar findings were revealed by another report that observed higher circulating concentrations of leptin and IGF-1 in excess abdominal fat [13]. In the experimental animals (mice) administration of recombinant leptin induced a three-fold increase in liver-derived IGF-1 [7]. Moreover, an in vitro study showed that the addition of leptin increased the expression of IGF-1 in MDA-MB-361 and SK-BR-3 breast cancer cell-lines [14].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were revealed by another report that observed higher circulating concentrations of leptin and IGF-1 in excess abdominal fat [13]. In the experimental animals (mice) administration of recombinant leptin induced a three-fold increase in liver-derived IGF-1 [7]. Moreover, an in vitro study showed that the addition of leptin increased the expression of IGF-1 in MDA-MB-361 and SK-BR-3 breast cancer cell-lines [14].…”
Section: Introductionsupporting
confidence: 86%
“…Leptin is closely linked with several growth factors such as vascular endothelial growth factor (VEGF), fibroblast growth factor 21 (FGF21), and insulin-like growth factor-1 (IGF-1) [5], [6], [7] (Table 1) [1], [4], [8], [9], [10], [11]. A study on human subjects detected an increased gene expression of leptin and IGF-1 in the subcutaneous fat of the obese group, while the expression of IGF-1 in the visceral fat was higher in the control group (non-obese cholecystectomy cases) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is an appetite-suppressive adipokine that links food intake with energy expenditure and body composition. 27 Leptin is known to increase muscle mass by decreasing the expression of atrophy-related factors such as myostatin, MuRF1, and muscle atrophy F-box in muscles, 28 possibly by regulating IGF1 levels, 29 although we found no significant correlation between serum leptin and IGF1 levels in our cohort ( Table 3). Changes in leptin sensitivity with ageing could contribute to the age-related degeneration of multiple organs, including skeletal muscles.…”
Section: Discussionmentioning
confidence: 57%
“…Leptin is mainly produced by adipocyte304647. Studies have also shown leptin production by other tissues, including skeletal muscle4849. Thus, we checked Leptin expression in Leptin- expressing tissues iWAT and Sk.M, and Ppar-γ expression in all the three tissues by normalized with the recommended gene pair, most and least stable gene, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%